1998
DOI: 10.1016/s0741-5214(98)70086-2
|View full text |Cite
|
Sign up to set email alerts
|

Activated protein C resistance in patients with peripheral vascular disease

Abstract: The factor V Leiden gene mutation and abnormal APC ratios are significantly increased in patients with lower extremity peripheral vascular disease and failed reconstructions. An abnormal APC ratio was seen without factor V Leiden gene mutation in 37% of patients with peripheral vascular diseases, suggesting additional causes of an abnormal APC ratio, exclusive of gene mutation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 24 publications
(51 reference statements)
2
24
0
Order By: Relevance
“…Depending on which APC resistance assay is used and what patient population is studied, up to 37% of patients with an abnormal APC resistance test do not have factor V Leiden [4]. An abnormal APC resistance test can also be due to a lupus anticoagulant and other, yet unknown, causes, and should, therefore, always be followed by the genetic test [5].…”
Section: Clinical Relevancementioning
confidence: 99%
See 1 more Smart Citation
“…Depending on which APC resistance assay is used and what patient population is studied, up to 37% of patients with an abnormal APC resistance test do not have factor V Leiden [4]. An abnormal APC resistance test can also be due to a lupus anticoagulant and other, yet unknown, causes, and should, therefore, always be followed by the genetic test [5].…”
Section: Clinical Relevancementioning
confidence: 99%
“…3 Probably reliable, but limited data in literature. 4 Test often positive or elevated at time of acute thrombosis, but subsequently negative [47]. 5 While many test kits used for lupus anticoagulant testing contain a heparin neutralizer that inactivates unfractionated heparin (UF) and possibly low molecular weight heparin (LMWH) thus making these tests reliable on UF and LMWH, clinicians needs to inquire with their laboratory how their individual test kit performs in samples with UF and LMW H. 6 No indication for testing in the acute setting provide education and support, advocate for those who are affected by, or at risk for blood clots, and to foster research.…”
Section: Patient Education Materials and Resourcesmentioning
confidence: 99%
“…11 12 Three studies have examined the role of factor V Leiden in patients with peripheral vascular disease. [13][14][15] The prevalence of factor V Leiden was found to be increased in all three studies in patients with peripheral vascular disease but, when based on APC resistance measurements, the prevalence varied between 11.6% and 41% of patients with aortoiliac disease using DNA analysis. A small study from Bristol concluded that factor V Leiden was not an important factor in the outcome of infrainguinal bypass grafting.…”
Section: Factor V Leidenmentioning
confidence: 82%
“…2) enhances protein C activation and also can translocate APC to the cell nucleus, where it presumably could con- 31 tribute to anti-inflammatory signalling [see Esmon,this issue,and ref. 24].…”
Section: Antithrombotic Protein C Pathwaymentioning
confidence: 99%